Ultrasound-guided peripheral abdominal wall blocks (Clinics, 2021)
The practice of regional anesthesia is in a state of progressive evolution, mainly due to the advent of ultrasound as an anesthesiologist’s instrument. Alternative techniques for postoperative analgesia of abdominal surgeries, such as transversus abdominis plane block, oblique subcostal transversus abdominis plane block, rectus abdominis muscle sheath block, ilioinguinal and iliohypogastric nerve block, and quadratus lumborum plane block, have proven useful, with good analgesic efficacy, especially when neuroaxial techniques (spinal anesthesia or epidural anesthesia) are not possible. This review discusses such blockades in detail, including the anatomical principles, indications, techniques, and potential complications.